Framing the ZDF’s November/December 2017 operation restore legacy: the case of the Herald and Daily News - Mudhumo, Linda Dadiso (Midlands State University, 2020)
The study interrogates the framing of the Zimbabwe Defence Forces (ZDF)’s November/December 2017 Operation Restore Legacy in The Herald and Daily News. It seeks to explore the frames the two newspapers used and why they used them. The study is informed by framing theory but gathers data through archival research. The study established that two newspapers under study realised contrasting frames on the nature of the operation restore legacy, with Daily News saying it was a coup and The Herald denying that the operation was a military takeover. Daily News regarded the operation restore legacy as a ZANU-PF Lacoste factional agenda and a necessary evil. The study also established The Herald showed some inconsistencies in showing who they were really in support of during the operation. The papers however had also some level of convergence which is the celebration of Mugabe’s fall from grace. The above issues realised by these two newspapers confirms the ideas that the state controlled media are used as mouth piece of the government and ruling party while privately media are critical of these two. The research also shows the relationship between military The Herald and Daily News’ coverage. The research analysed data through qualitative content analysis and critical discourse analysis as well as presenting it in thematic form.